BISIKAN DARI BALIK LAYAR: NETNOGRAFI STRATEGI BISNIS BERORIENTASI PASAR - Edi Purwanto; John J.O.I. Ihalauw (Universitas Bunda Mulia, 2016)
Netnography is an interpretative approach to study consumer behavior from different cultures andcommunities in the cyberspace or Internet. The approach was also called as a “digital ethnography”or “virtual ethnography”. As a marketing research technique, “netnography” uses the informationsources published in the online forums. This research uses the reviews on zomato.com as a source ofdata to assess the market orientation development in business practice, especially at Restaurant X.The result of netnography analysis indicates that customer orientation, competitor orientation, interfunctionalcoordination and long-term focus are the dimensions of market orientation and should bedeveloped for customer satisfaction and loyalty leading forward to the business performance.